A Systematic Literature Review of Work-Life Fulfillment and Future Research Implications - Shukla, Shalu; Khatri, Puja (Prabandhan: Indian Journal of Management, 2023)
Purpose : The present study systematically reviewed the literature to conceptually develop the construct of work-life fulfillment by identifying its dimensions, antecedents, and outcomes. The study was motivated by the growing calls of management and organizational psychology scholars, emphasizing work-life fulfillment as the solution to several problems experienced by employees, like burnout, engagement, and work-life imbalance. Methodology : The four-step PRISMA (Preferred Reporting Items for Systematic Reviews and Meta- Analyses) technique was used to select 64 articles for review. The ADO (antecedents, dimensions, and outcomes) framework was used to analyze the selected papers. Findings : The study contributed a unique conceptualization of work-life fulfillment by identifying its definitions, dimensions, antecedents, and outcomes. The definition and dimensions presented allow for the development of a psychometric measure. The study highlighted other avenues for future research and development of theory. Practical Implications : The identified dimensions and antecedents of work-life fulfillment can be utilized by the management to develop HR strategies and design training programs to ensure the holistic fulfillment of employees. Apart from materialistic rewards, organizations should focus on fulfilling employees’ self-actualization and self-transcendence needs. By facilitating professional and personal aspirations, organizations should reap the benefits of a motivated workforce, prevent burnout, and promote well-being. Originality : The research was original as it adopted an integrated approach to study individual fulfillment in both the personal and professional domains, departing from the earlier fragmented approach.